Interleukin-17a Induces Neuronal Differentiation of Induced-Pluripotent Stem Cell-Derived Neural Progenitors From Autistic and Control Subjects - Gomes, Ana Karolyne Santos; Dantas, Rafaelly Mayara; Yokota, Bruno Yukio; Silva, André Luiz Teles e; Griesi-Oliveira, Karina; Passos-Bueno, Maria Rita; Sertié, Andréa Laurato (Frontiers in Neuroscience, 2022)
Prenatal exposure to maternal immune activation (MIA) has been suggested to increase the probability of autism spectrum disorder (ASD). Recent evidence from animal studies indicates a key role for interleukin-17a (IL-17a) in promoting MIA-induced behavioral and brain abnormalities reminiscent of ASD. However, it is still unclear how IL-17a acts on the human developing brain and the cell types directly affected by IL-17a signaling. In this study, we used iPSC-derived neural progenitor cells (NPCs) from individuals with ASD of known and unknown genetic cause as well as from neurotypical controls to examine the effects of exogenous IL-17a on NPC proliferation, migration and neuronal differentiation, and whether IL-17a and genetic risk factors for ASD interact exacerbating alterations in NPC function. We observed that ASD and control NPCs endogenously express IL-17a receptor (IL17RA), and that IL-17a/IL17RA activation modulates downstream ERK1/2 and mTORC1 signaling pathways. Exogenous IL-17a did not induce abnormal proliferation and migration of ASD and control NPCs but, on the other hand, it significantly increased the expression of synaptic (Synaptophysin-1, Synapsin-1) and neuronal polarity (MAP2) proteins in these cells. Also, as we observed that ASD and control NPCs exhibited similar responses to exogenous IL-17a, it is possible that a more inflammatory environment containing other immune molecules besides IL-17a may be needed to trigger gene-environment interactions during neurodevelopment. In conclusion, our results suggest that exogenous IL-17a positively regulates the neuronal differentiation of human NPCs, which may disturb normal neuronal and synaptic development and contribute to MIA-related changes in brain function and behavior.